2009
DOI: 10.1002/ijc.24747
|View full text |Cite
|
Sign up to set email alerts
|

Clinical whole‐body skin examination reduces the incidence of thick melanomas

Abstract: Survival from melanoma is strongly related to tumour thickness, thus earlier diagnosis has the potential to reduce mortality from this disease. However, in the absence of conclusive evidence that clinical skin examination reduces mortality, evidencebased assessments do not recommend population screening. We aimed to assess whether clinical whole-body skin examination is associated with a reduced incidence of thick melanoma and also whether screening is associated with an increased incidence of thin lesions (po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
170
0
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 177 publications
(182 citation statements)
references
References 26 publications
5
170
0
7
Order By: Relevance
“…In addition, we found a higher risk of thick melanoma among those who were retired and among those who were not currently married or living as married. We have previously reported 6 that CSE in the past 3 years significantly reduces the risk of thick melanoma, and the results here suggest that it may be a mediator between education and melanoma thickness.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In addition, we found a higher risk of thick melanoma among those who were retired and among those who were not currently married or living as married. We have previously reported 6 that CSE in the past 3 years significantly reduces the risk of thick melanoma, and the results here suggest that it may be a mediator between education and melanoma thickness.…”
Section: Discussionsupporting
confidence: 71%
“…Because CSE is independently related to lower risk of thick melanoma, 6 this association is enhanced further, as those with higher education are also more likely to participate in CSE. As survival from melanoma is strongly related to melanoma thickness, these results suggest that a thorough understanding of how education and other measures of SES impact on melanoma thickness and CSEs should be a research priority.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Another study with similar findings was performed in Australia in 2008. This case-control study demonstrated a 38% increase in the probability of a thin melanoma (<0.75 mm) being identified and that pre-diagnosis WBE screening leads to a 14% risk reduction of thick melanoma (>0.75 mm) diagnosis (5).…”
Section: Screening Recommendationsmentioning
confidence: 66%
“…Like most other neoplastic conditions, known risk factors of melanoma include genetic defects, environmental exposure, and a combination of both (5). Although multiple genetic syndromes incur a significantly increased risk for the development of cutaneous malignancy (discussed later), inherited phenotypic traits associated with melanoma include fair skin, light hair, red hair, freckles, and light eye color.…”
Section: General Risk Factorsmentioning
confidence: 99%